Magnetic Resonance Imaging of gas hydrate formation and conversion at sub-seafloor conditions - Kossel, Elke; Deusner, Christian; Bigalke, Nikolaus; Haeckel, Matthias (Diffusion Fundamentals, 2013)
The production of natural gas from sub-seafloor gas hydrates is one possible strategy to meet the world’s growing demand for energy. On the other hand, climate warming scenarios call for the substitution of fossil energy resources by sustainable energy concepts. Burning natural gas from gas hydrates could be emission neutral if it was combined with a safe storage of the emitted CO2. Laboratory experiments, that address corresponding strategies, need to be performed under high pressures and low temperatures to meet the thermodynamic conditions of the sub-seafloor environment. In this paper, we present a high-pressure flow-through sample cell that is suitable for nuclear magnetic resonance (NMR) experiments at realistic marine environmental conditions, i.e. pressures up to 15 MPa and temperatures from 5 to 20°C, and we demonstrate its suitability in applied gas hydrate research.